201k views
2 votes
By definition, (fog)(x) = f(g(x))So if g(2) = 3 and f(3) = 16, then (fog)(2) =

By definition, (fog)(x) = f(g(x))So if g(2) = 3 and f(3) = 16, then (fog)(2) =-example-1
User Niya
by
5.2k points

1 Answer

3 votes

Answer:


(f\circ g)(2)=16

Explanation:

By definition composite function would be:


(f\circ g)(x)=f(g(x))

Then, if g(2)=3 and f(3)=16, therefore for f(g(x)):


\begin{gathered} (f\circ g)(x)=f(g(2))=f(3) \\ \text{Hence,} \\ (f\circ g)(2)=16 \end{gathered}

User Ixrock
by
5.2k points